Strategi Pembelajaran Kolaboratif SD Meningkatkan Keterampilan Sosial dan Keterlibatan Siswa - Anisa Mulia Maharani; Nayla Zhalfa Andari; Ari Suriani (Journal Innovation In Education, 2025)
This study explores the various ways in which collaborative learning approaches can be implemented in elementary schools (SD) to improve students’ social skills and participation during the learning process. Collaborative learning encourages students to work together in small groups, discuss, and solve problems together to improve communication, cooperation, and social responsibility. Through literature research and observation, it was found that this method is effective in improving students’ social skills, such as better communication, respecting friends’ opinions, and increasing their desire to be more active in game activities. You can create a good and enjoyable learning environment by using collaborative learning strategies. Finally, it will significantly increase students’ participation. Some of the challenges found include limited learning resources and teachers’ lack of understanding of collaborative methods. Therefore, teachers should be trained and provided with supporting tools to maximize the use of this strategy. Thus, collaborative learning is a great way to increase students’ engagement and improve their social skills in elementary schools. Overall, it improves the quality of learning.